Analysis Of Leadership Style At Public Works And PUPR Office, Sumedang District - Sarah Fergiania Azahra; Desan Henriawan (SINTESA, 2023)
This research focuses on Leadership Style in the Public Works and Public Housing (PUPR) Office of Sumedang Regency with the aim of knowing the leadership style used by the head of the service and its development efforts. The research method used was qualitative with a purposive sampling technique and informants were taken from service secretaries, heads of fields, and others. The data analysis technique uses Miles and Huberman and the results of interviews, observation and analysis show that the leadership style used is good and in accordance with regulations, and the leadership style used is democratic with good communication, decisions are taken through deliberation, transparency in communication, and good relationships between superiors and subordinates.